The Survivorship Bias, Share Price Effect and Small Firm Effect in Malaysian Markets - Tan, Siew Ngoh (2007)
This study aims to examine the relation between average returns, firm size, and price levels for Malaysian stocks after controlling for survivorship bias from the period 1995 to 2003. This period consist of pre-economy crisis 1995-1996, during economy crisis 1997-1998, and post economy crisis 1999-2006. The main objective of the study was to examine the small firm size effect for difference proce levels in Malaysian market. The study employed a sample of 272 stocks listed in the Kuala Lumpur Stock Exchange (KLSE) main board. The results for each portfolio were then compared across the three different study periods, which is pre-economy crisis, during economy crisis, and post-economy crisis. The finding indicates that there is a significant inverse share price level effect in Malaysia markets before the economy crisis and during the economy crisis periods. However the inverse share price level effect is not significant after the economy crisis. evidence that supports the small firm size effect is less clear for Malaysian stocks. While the findings were not conclusive, the firm size stocks did not provide a clear trend and relation with stocks returns with a different price level. the small firm portfolio appeared much volatile than the large firm size stocks during the financial crisis period. As a whole, the study calls for cautions use of firm size as dominate indicators and factors for investment consideration and decision in Malaysia market.